Network Analysis and Design - Yusof, R. (Penerbit Universiti. KUTKM, 2007)
The objectives of this module is to enable the student to fully understand the topics covered in Network Analysis and Design (NAD) subject through extensive tutorial and introduce student to NAD's software using the top design software tool in the industry namely Microsoft Visio 2003. This software will help student in understanding and applying the network analysis and design areas and processes. We will also use other tools such as documentation software which is Microsoft Word, Internet Browsers and Paint Brush. Each lab offers student many opportunities to get hands-on and build new software skills.